Музейна збірка кераміки Михайла Китриша як ілюстрація гончарних традицій Опішного 1970-х–2010-х років - Ликова, О.Г. (Сіверщина в історії України, 2020)
У Національному музеї-заповіднику українського гончарства
в Опішному зберігається найбільша персональна колекція кераміки Михайла Китриша в Україні. У статті проаналізовано склад
колекції, виділено основні морфологічні групи виробів майстра.
На прикладі виробів, що наповнюють цю збірку, виділено типові
форми і основні елементи декору, що використовували опішненські гончарі у зазначений період. Акцентовано увагу на проблемі
атрибутування гончарних виробів у колекції. Визначено способи
і шляхи усунення спірних питань в атрибуції. The article is devoted to the ceramics of Mykhailo Kytrysh, a prominent
potter from Opishne, whose work of 1999 was awarded by the State
Prize of Ukraine named after Taras Shevchenko. The basis for the analyst’s
study is the personal collection of ceramics, which is formed in the funds
of the National Museum of Ukrainian Pottery in Opishne. The collection
of pottery is estimated at 320 units. The works to be collected, to increase
the number of works of the master - tableware, zoomorphic sculptures,
vases, plates, ritual objects, a toy. Author was a potter of the 1960s at the
Opishne ceramics factory. Admirable rice art union of Mykhailo Kytrysh’s
work was the eating of different coloring watering in robots. The creative
maestro will be working at the artistic and experimental creative laboratory
factory, where he will spend an hour for experimentation. This decoration
has become a visit of Mykhailo Kytrysh’s creative work.
Mykhailo Kytrysh has developed various methods for decorating the
surfaces of goods - with contouring, ritual elements and applying the decor.
Decorations are designed to endure the growth of motivation. Contour
grinding is broadened in pottery by Opishne’s at the XX century and
on the beginning of the XXI century table is already respected traditional
for the Moscow pottery. Mykhhailo Kytrysh’s dishes are decorated in
the same way. The zoomorphic sculptures, vases and peasants of the author
are decorated with applied elements of urban watering, which in turn
gives an uncompromising enemy effect.
Mykhailo Kytrysh’s ceramics collectors at the National museum of
Ukrainian pottery are taking revenge on the traditional detached pottery
of the XXth century, so it is an innovation, which has become a sublime
richness of his work. Traditionalist was shown, it is important, in the chicory
forms of dishes, which were prepared in the Opishne ancestral table,
and in the decoration of his contoured young growth ornaments, which
traditionally produced the potter’s wife.